1985
DOI: 10.1159/000199183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deoxycholic Acid on the Tumour Incidence, Distribution, and Receptor Status of Colorectal Cancer in the Rat Model

Abstract: It has previously been observed that 25% of human colorectal cancers contain specific receptors to deoxycholic acid (DCA). In the present study, the effect of intrarectal instillation of DCA on tumour number, distribution, size, and DCA receptor status was measured in rats receiving the colorectal carcinogen, azoxymethane. Rats treated with azoxymethane and intrarectal DCA developed significantly more colorectal cancers than rats receiving azoxymethane and intrarectal saline (median 11.5, range 8–17 vs. median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…[8][9][10][11][12][13] There may be a possibility that the formation of an DCA-adduct with a crucial protein, e.g., histone, causes such a malignant physiological effect. Indeed, it has been exhibited that LCA binds to lysine residues of histone in colonic mucosa epithelial cells, resulting in denaturation of the DNA double strand.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] There may be a possibility that the formation of an DCA-adduct with a crucial protein, e.g., histone, causes such a malignant physiological effect. Indeed, it has been exhibited that LCA binds to lysine residues of histone in colonic mucosa epithelial cells, resulting in denaturation of the DNA double strand.…”
Section: Resultsmentioning
confidence: 99%
“…Secondary bile acids, as deoxycholic and lithocholic acids, have a promoting effect on chemically induced colon cancer in rats (Narisawa et al, 1974;Reddy & Watanabe, 1979;Summerton et al, 1985) and secondary bile acids are also cytotoxic to colonic cells and may damage DNA (Cheah & Bernstein, 1990), resulting in an increased cell proliferation (Lapre  & Van der Meer, 1992). A lowered concentration of bile acids and a reduced Corn starch for ileostomy patients AM Langkilde et al conversion of primary bile acids to secondary bile acids in the colon are therefore considered to constitute one of the mechanisms behind a protective effect against colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The primary BA, cholic and chenodeoxycholic acid, are converted by 7a-dehydroxylation into their corresponding secondary BA. deoxycholic and lithocholic acid [11,12], In numerous experimental studies, secondary bile acids have been shown to be potent pro moters of colorectal cancer [6,7,13,14], Bacterial BA metabolism in the human large intestine, however, may be influenced by dietary components. Dietary fiber has been shown to reduce fecal concentrations of sec ondary BA, an effect which was mostly attrib uted to the bulking effect of fiber [15][16][17], Malabsorbed starch, however, may act in a different way.…”
mentioning
confidence: 99%